2013
DOI: 10.1097/psy.0b013e31828c4524
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Primary Sexual Reward Manipulation on Cortisol Responses to Psychosocial Stress in Men

Abstract: This research provides the first evidence linking the experience of reward with reduced stress reactivity in humans and suggests a potential novel reward pathway for coping under stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…High cortisol has been associated with enhanced reward sensitivity (Oswald et al, 2005 ) and dopamine is released in the ventral striatum proportionally to cortisol reactivity to a stressor (Pruessner et al, 2004 ). Conversely, reward has been associated with reduced cortisol reactivity (Creswell et al, 2013 ). The systems appear to be intricately related, and skydiving proffers a unique opportunity to examine how cortisol response relates to subjective reward.…”
Section: Discussionmentioning
confidence: 99%
“…High cortisol has been associated with enhanced reward sensitivity (Oswald et al, 2005 ) and dopamine is released in the ventral striatum proportionally to cortisol reactivity to a stressor (Pruessner et al, 2004 ). Conversely, reward has been associated with reduced cortisol reactivity (Creswell et al, 2013 ). The systems appear to be intricately related, and skydiving proffers a unique opportunity to examine how cortisol response relates to subjective reward.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that men who flipped through mildly erotic pictures of mixed couples had significantly lower cortisol reactivity to a subsequent stress test than the controls, and they did a lot better in a maths test. 26 In younger men, porn use may help them explore their sexuality, find out what they like, and boost their confidence in knowing what to do with real-life partners. While concerns exist regarding the unrealistic nature of some porn, a survey of 18-25-yearolds in Great Britain found that almost three-quarters of men considered the sex in porn not reflective of real life, and almost half agreed that porn content is creating 'impossible' beauty standards.…”
Section: Impact Of Porn Viewing On Menmentioning
confidence: 99%
“…Soft porn has also been found to relieve psychosocial stress. One study found that men who flipped through mildly erotic pictures of mixed couples had significantly lower cortisol reactivity to a subsequent stress test than the controls, and they did a lot better in a maths test 26 …”
Section: Impact Of Porn Viewing On Menmentioning
confidence: 99%
“…Translational and human research has consistently shown that increased reward manipulations and rewarding environments promote the growth of stress resilience (Dutcher and Creswell, 2018). Much of this research has analyzed the stress buffering effects of primary rewards using food, drink, or sex (Abad et al, 1996;Christiansen et al, 2011;Creswell et al, 2013). However, there is also emerging evidence that visual art interventions can enhance functional connectivity related to psychological resilience (Bolwerk et al, 2014), can lower levels of salivary cortisol and of self-reported measure of stress (Clow and Fredhoi, 2006) and even decrease systolic blood pressure (Mastandrea et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…The reward pathway activation observed as a consequence of visual art exposure can be beneficial as reward activation has shown to modulate survival behaviors by reducing stress levels. Even brief exposure to reward stimuli (such as erotic images) can decrease cortisol reactivity, improving cognitive performance on social stress tasks (Creswell et al, 2013).…”
Section: Reward Areas Activated By Art and Their Connection To The Stress Responsive Systemmentioning
confidence: 99%